2008
DOI: 10.1002/anie.200802805
|View full text |Cite
|
Sign up to set email alerts
|

A Polymeric Pseudorotaxane Constructed from Cucurbituril and Aniline, and Stabilization of Its Radical Cation

Abstract: Picking up the thread: A polypseudorotaxane 1 with a regular one‐dimensional linear structure has been constructed in satisfactory yield from cucurbit[7]uril and polyaniline (PANI). The complexation with cucurbituril not only enhances the water solubility of the PANI (see picture; after 10 h), but also effectively stabilizes its radical cation form, that is, the conductive doped form, as shown by EPR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 71 publications
2
74
0
1
Order By: Relevance
“…1.5 nm) of PANi/CB [7] fibres are consistent with the outer diameter of CB [7]. A schematic possible structure of PANi-CB [7] is presented in Figure.4,e) [55]. Therefore, the interchain interactions could be avoided by keeping the chains at a distance determined by the thickness of macrocycles, and the electronic properties could be studied for a single conjugated chain.…”
Section: < Insert Figure 4 >supporting
confidence: 55%
See 2 more Smart Citations
“…1.5 nm) of PANi/CB [7] fibres are consistent with the outer diameter of CB [7]. A schematic possible structure of PANi-CB [7] is presented in Figure.4,e) [55]. Therefore, the interchain interactions could be avoided by keeping the chains at a distance determined by the thickness of macrocycles, and the electronic properties could be studied for a single conjugated chain.…”
Section: < Insert Figure 4 >supporting
confidence: 55%
“…A polymeric pseudorotaxane based on cucurbit [7]uril and polyaniline has been reported by Liu et al [55 ]. Using NMR the authors calculated that every repeating unit contains three aniline units and one CB [7] macrocycle, as shown in Scheme 9 [55].…”
Section: Polyanilinesmentioning
confidence: 94%
See 1 more Smart Citation
“…The experimental results revealed that it was different in the interaction models of the formed host-guest inclusion complexes between the cucurbit [7]uril with the four guests and the cucurbit [8]uril with the four guests. The cucurbit [7]uril preferred to thread on the linear guests and formed pseudorotaxane-like or "dumbbell"-like inclusion complexes, while the cucurbit [8]uril preferred to included whole body of a guest in a fold manner due to having a larger cavity. Keywords cucurbit [7,8] [27] .…”
Section: Key Laboratory Of Chemistry For Natural Products Of Guizhou mentioning
confidence: 95%
“…The cucurbit [7]uril preferred to thread on the linear guests and formed pseudorotaxane-like or "dumbbell"-like inclusion complexes, while the cucurbit [8]uril preferred to included whole body of a guest in a fold manner due to having a larger cavity. Keywords cucurbit [7,8] [27] . 为了进一…”
Section: Key Laboratory Of Chemistry For Natural Products Of Guizhou mentioning
confidence: 99%